2018
DOI: 10.1371/journal.pone.0193233
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory, large-scale study of pain and quality of life outcomes in cancer patients with moderate or severe pain, and variables predicting improvement

Abstract: BackgroundThere have been few large-scale, real world studies in Spain to assess change in pain and quality of life (QOL) outcomes in cancer patients with moderate to severe pain. This study aimed to assess changes on both outcomes after 3 months of usual care and to investigate factors associated with change in QoL.Patients and methodsLarge, multi-centre, observational study in patients with lung, head and neck, colorectal or breast cancer experiencing a first episode of moderate to severe pain while attendin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 32 publications
(28 reference statements)
0
16
0
Order By: Relevance
“…Chemotherapy might be associated with poorer QoL in CRC patients. [175] However, a significant association was observed in this cohort only in patients receiving oxaliplatin, who also reported more severe numbness/tingling. Patients' experience of numbness/tingling was associated with impaired physical QoL.…”
Section: Symptom Burden and Qol And Associated Factorsmentioning
confidence: 55%
See 2 more Smart Citations
“…Chemotherapy might be associated with poorer QoL in CRC patients. [175] However, a significant association was observed in this cohort only in patients receiving oxaliplatin, who also reported more severe numbness/tingling. Patients' experience of numbness/tingling was associated with impaired physical QoL.…”
Section: Symptom Burden and Qol And Associated Factorsmentioning
confidence: 55%
“…[ The MSAS includes the symptoms worrying and sadness, but not depression, [174] which affects QoL. [94,175] To assess depression, the SCQ-19, which contains the question "Are you depressed?" and information regarding medical treatment for depression, was used in the thesis research.…”
Section: Measuring Symptoms With the Msasmentioning
confidence: 99%
See 1 more Smart Citation
“…These two studies were analysed separately because the time since diagnosis could not be derived. The other four studies with repeated measures all reported loss to follow-up at each evaluated time point [40,46,50,52].…”
Section: Critical Appraisalmentioning
confidence: 99%
“…Correspondingly, most men experience initial declines in HRQoL in the 2 years following their treatment; there is little change in years 3-10, and most differences between treatments attenuated over time (Punnen et al, 2015). On the other hand, a Spanish study in patients with lung, head, neck, colorectal, or breast cancer reported that after 3 months of usual care, there was a significant improvement in pain and the quality of life (Maximiano et al, 2018). Our findings show that clinically significant changes in HRQoL were not found in this study.…”
Section: Discussionmentioning
confidence: 99%